Mechanical characterization of a flexible epoxy adhesive for the design of hybrid bonded-bolted joints. (October 2019) - Lim, Gyu-Hyeong; Heidari-Rarani, Mohammad; Bodjona, Kobye; Raju, Karthik Prasanna; Romanov, Valentin; Lessard, Larry
Abstract: Hybrid bolted/bonded joints are less effective when designed with strong structural adhesives as insignificant load is introduced to the bolt before the bond reaches failure. Advancement in hybrid joint design requires further knowledge on the behavior of flexible adhesives, which involve significant complexities such as large inelastic deformation. This study investigates the mechanical properties of EA9361 AERO, a representative flexible epoxy adhesive, within the context of the design of hybrid bolted/bonded joints. Tensile and shear tests were performed to obtain the tensile stress/strain relation, strength, strain-to-failure, Poisson's ratio, and adhesive's responses under pure shear state. A practical methodology for strain measurement of a thin bondline of adhesive was proposed using digital image correlation (DIC). It was concluded that the nonlinear tensile stress/strain relation of the flexible adhesive can be accurately represented with a bilinear elastic/plastic material model. The Poisson's ratio was found to significantly change throughout the strain development. Highlights: Mechanical properties of EA9361 AERO, a representative flexible epoxy adhesive are characterized. A practical methodology for strain measurement of a thin bondline of adhesive was proposed using DIC. The nonlinear tensile stress/strain relation of the flexible adhesive can be represented with an elastic/plastic model. The Poisson's ratio was found to significantly change throughout the strain development.